An Analytic Solution for a Vasicek Interest Rate Convertible Bond Model - A. S. Deakin; Matt Davison (Journal of Applied Mathematics)
This paper provides the analytic solution to the partial differential equation for the value of a convertible bond. The equation assumes a Vasicek model for the interest rate and a geometric Brownian motion model for the stock price. The solution is obtained using integral transforms.